optical proprties of poly crystaline CdS thin films - Baghdad Science Journal (مجلة بغداد للعلوم, 2005)
Studied the optical properties of the membranes CdS thin containing different ratios of ions cadmium to sulfur attended models manner spraying chemical gases on the rules of the glass temperature preparation (350c) were calculated energy gap allowed direct these membranes as observed decrease in the value of the energy gap at reducing the proportion ofsulfur ions as absorption coefficient was calculated